The Influence of Green Perceived Value, Risk and Quality toward Green Purchase Intention through Green Trust - Zulfanizy, Kresno; Wahyono, Wahyono (Management Analysis Journal, 2019)
Consumens concern for environmental sustainability raises consumption behavior for environmentally friendly products and encourages companies to implement green marketing strategies. The aim of this research is to examine the effect of green perceived value and green perceived risk toward green purchase intention via green trust as mediator variable (intervening). The population of this research is all consumers of UKM products in the city of Semarang. The sampel is 100 respondents used convenience sampling technique. The data collecting method used questionnaire. The data analysis used Path Analysis with SPSS v21.T he results showed that green perceived value and green perceived quality had a significant positive effect on green purchase intention while green perceived quality had a significant negative effect on the green purchase intention. Green trust has a role as an intervening variable between the variables green perceived value, green perceived risk and green perceived quality towards the green purchase intention. The conclusions of this research are there is an effect of green perceived value and green perceived risk toward green purchase intention via green trust.